2016
DOI: 10.1159/000445566
|View full text |Cite
|
Sign up to set email alerts
|

Use Dependent Attenuation of Rat HCN1-Mediated Ih in Intact HEK293 Cells

Abstract: Background/Aims: Cationic currents (Ih) through the fast activating and relatively cAMP insensitive subtype of hyperpolarization-activated cyclic nucleotide-gated (HCN) channels, HCN1, are limited by cytosolic factors in mammalian cells. This cytosolic HCN1 break is boosted by changes in membrane voltage that are not characterized on a biophysical level, yet. Methods: We overexpressed rat (r)HCN1 in human embryonic kidney cells (HEK293) and recorded pharmacologically isolated Ih in cell-a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
5
6
0
Order By: Relevance
“…Voltage-dependent hysteresis of I h is thought to exhibit a substantial role in influencing the electrical behavior of electrically excitable cells such as GH 3 cells. In agreement with previous observations [42][43][44], the I h natively existing in GH 3 cells was described to undergo either a hysteretic change in its voltage dependence, or a mode shift in which the voltage sensitivity in gating charge movements of the current depends on the previous state of the channel [42,43]. In this study, we also examined the possible perturbations of OXAL on such a non-equilibrium property of I h in GH 3 cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Voltage-dependent hysteresis of I h is thought to exhibit a substantial role in influencing the electrical behavior of electrically excitable cells such as GH 3 cells. In agreement with previous observations [42][43][44], the I h natively existing in GH 3 cells was described to undergo either a hysteretic change in its voltage dependence, or a mode shift in which the voltage sensitivity in gating charge movements of the current depends on the previous state of the channel [42,43]. In this study, we also examined the possible perturbations of OXAL on such a non-equilibrium property of I h in GH 3 cells.…”
Section: Discussionsupporting
confidence: 81%
“…The voltage-dependent hysteresis of Ih has been previously demonstrated to exert a high influence on electrical behaviors such as action potential (AP) firing [42][43][44]. For this reason, we further explored whether there is possible voltage-dependent hysteresis existing in Ih recorded from GH3 cells.…”
Section: The Effect Of Oxal On Voltage-dependent Hysteresis Of Ih Elimentioning
confidence: 97%
“…The voltage-dependent hysteresis of I h has been shown to exhibit substantial role in influencing electrical behavior of electrically excitable cells such as GH 3 cells. In keeping with previous observations [25][26][27], the I h identified in GH 3 cells was found to undergo either a hysteresis in its voltage dependence, or mode shift in which the voltage sensitivity of gating charge movements relies on the previous state [26,27]. In this study, we also examined possible perturbations of croton-03 on such non-equilibrium property of I h in GH 3 cells.…”
Section: Discussionsupporting
confidence: 75%
“…The voltage-dependent hysteresis of ionic currents (e.g., I h ) has been previously demonstrated to exert a significant impact on electrical behaviors such as the firing of action potentials [25][26][27]. For this reason, we further explored whether there is possible voltage-dependent hysteresis existing in I h recorded from GH 3 cells.…”
Section: Effect Of Croton-03 On the Voltage-dependent Hysteresis Of Imentioning
confidence: 98%
“…It has been previously demonstrated that the voltage-dependent hysteresis of I h density can exert a high influence on electrical behaviors such as action potential firing [41,[44][45][46]. As such, we further explored whether HNK could perturb the voltage hysteresis of this current density identified in GH 3 cells.…”
Section: Effect Of Hnk On Voltage-dependent Hysteresis Of I H Elicitementioning
confidence: 93%